2017
DOI: 10.1103/physrevaccelbeams.20.082801
|View full text |Cite
|
Sign up to set email alerts
|

Reversible beam heater for suppression of microbunching instability by transverse gradient undulators

Abstract: The microbunching instability driven by beam collective effects in a linear accelerator of a free-electron laser (FEL) facility significantly degrades the electron beam quality and FEL performance. A conventional method to suppress this instability is to introduce an additional uncorrelated energy spread by laser-electron interaction, which has been successfully operated in the Linac Coherent Light Source and Fermi@Elettra, etc. Some other ideas are recently proposed to suppress the instability without increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…We will assume the form K(x) = K 0 (1 + αx). The motion of a particle in the presence of such a field was analyzed in [26], in which they found that the motion could be described using a linear transfer matrix R with the key non-trivial elements being…”
Section: Analysis With An Added Transverse Gradient Undulatormentioning
confidence: 99%
See 1 more Smart Citation
“…We will assume the form K(x) = K 0 (1 + αx). The motion of a particle in the presence of such a field was analyzed in [26], in which they found that the motion could be described using a linear transfer matrix R with the key non-trivial elements being…”
Section: Analysis With An Added Transverse Gradient Undulatormentioning
confidence: 99%
“…We begin with simulations using ideal beams, meaning beams generated simply by explicitly applying the transformations given in Equations ( 23)- (26). We again consider three modulation amplitudes: A = 16.5, A = 34, and A = 50.…”
Section: Genesis Simulations Of Felmentioning
confidence: 99%
“…The longitudinal phase space smearing brought up by the coupling terms in BC1 can greatly smooth the upstream density and energy modulation, thus suppresses further instability amplification in the following transport system. Meanwhile, due to the existence of energy chirp before BC1, additional slice energy spread will also be induced by the transverse to longitudinal coupling terms, which is given as [21,25]:…”
Section: Microbunching Instability Mitigation Schemementioning
confidence: 99%
“…However, for seeded FELs it could degrade the FEL performance due to the increase of final electron beam energy spread [16]. Recently several new methods based on transverse-to-longitudinal coupling were proposed to suppress the microbunching instability [17][18][19][20][21]. These schemes are attractive because of the "reversible feature," which means the transverse emittance and slice energy spread can be recovered meanwhile effectively suppresses the microbunching instability [22].…”
Section: Introductionmentioning
confidence: 99%
“…The electron beam passing through the laser heater chicane attains extra uncorrelated energy spread from the laser induced energy modulation. Such a device provides an effective control of the electron beam uncorrelated energy spread and was widely adopted in most modern linear accelerator based x-ray FEL light sources [15,16,17,18,19] even though several different but less mature methods were proposed to mitigate the microbunching instability [20,21,22,23,24,25].…”
Section: Introductionmentioning
confidence: 99%